QUALITY OF LIFE IN THE PATHOLOGY OF THE CARDIOVASCULAR SYSTEM - Khusainova Munira Alisherovna; Bekmuradova Maxsuda Salhiddinovna; Hamrayeva Nasiba Abdurasulovna; Hayitov Safarali Maxammadiyevich (Scholar Express Journals, 2023)
To study the features of the psychoemotional state of middle-aged patients with acute coronary syndrome (ACS) without st segment elevation in the period of 6 months after hospitalization.
Keywords: myocardial infarction; gender characteristics; coronary heart disease in women; quality of life